Prosedur Penerbitan E-Visa Crew Kapal Safeen Station 5 pada Kantor Imigrasi Batam oleh PT. Menara Shipping Agency Batam - Claudya Pasha Riany; Syarifur Ridho; Netty Kesuma (KALAO'S MARITIME JOURNAL, 2025)
This paper is prepared with the objective of examining the stages and procedures involved in the issuance of e-visas for crew members assigned to Safeen Station 5 through PT. Menara Shipping Agency Batam. The process begins when the crew members perform sign on and continues through sign off, encompassing all activities from the arrival of the crew in Indonesia until their return to their respective home countries. In preparing this paper, the author applied a methodological approach through the implementation of Practical Training (Onshore Practice). Data were collected using two primary methods, namely field study and library study, in order to obtain an in-depth understanding of how PT. Menara Shipping Agency Batam carries out ship agency services, particularly in relation to the crew change process. PT. Menara Shipping Agency Batam is a company engaged in ship agency services, acting as a representative (shipping agency) responsible for handling various ship-related documents and operational requirements, including the process of crew replacement. In practice, one of the common obstacles encountered during the implementation of crew change procedures is miscommunication between the ship owner, the agent, and the relevant authorities. Therefore, effective synergy and coordination among all parties—especially between shipping companies and authorized government institutions—are essential to ensure the smooth execution of crew change services. The coordination referred to involves the clear division of roles and the optimal performance of functions by each institution, so that ship services can be carried out safely, efficiently, and without unnecessary obstacles.Field Study The field study method was conducted through direct observation at the company. Through this method, the author was able to directly observe the crew change handling process on several vessels and to ask questions to employees regarding matters that were not yet fully understood.